GE_GERICHTE A/1012/2024 vom 9. Dezember 2024 - GE Cour de justice (2024)
INDEMNITÉ DE DÉPART;PRESTATION EN CAPITAL;PRÉVOYANCE PROFESSIONNELLE | LIPP.18.al3; LIPP.43; LIPP.45.al2; LIFD.17.al2; LIFD.37; LIFD.38.al2